PENGARUH MOTIVASI KERJA, WORK LIFE BALANCE, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI PT. INDONESIA EPSON INDUSTRY - Shinshina Hurin’ina Rahman; Tri Mulyani Kartini (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
Employee performance is a key factor that determines the success of a company. Epson is known as a leading company in the field of technology and innovation. It is known that employee performance at PT Epson Industry is still relatively low due to several factors. An in-depth understanding of the factors that influence employee performance is very important. Work motivation, work-life balance, and workload are some of the factors that have a significant role in determining the productivity and effectiveness of the organization as a whole. This study aims to determine work motivation, work life balance and workload affect employee performance at PT Epson. This research is a type of quantitative research with causal associative research design. The sample of this study amounted to 222 respondents selected through stratified random sampling technique. The data were analyzed by Outer Model and Inner Mode). The results showed that work motivation has a significant positive effect on employee performance with a path coefficient of 0.45 (p-value = 0.000), work-life balance was also found to have a significant positive effect on employee performance with a path coefficient of 0.35 (p-value = 0.000) and workload has a significant negative relationship with employee performance with a path coefficient of -0.20 (p-value = 0.005). So it can be concluded that rewards, recognition, job satisfaction and work-life balance and workload affect the productivity and quality of employee results.